Tradisi Fenomenologi pada Penelitian Komunikasi Kualitatif: Sebuah Pengalaman Akademis - Kuswarno, Engkus (Mediator, 2006)
As a communication quantitative research, a phenomenological tradition in communication qualitative research has been divided in three important steps, such as preparation, implementation and reporting step. Researcher in the preparation step has a lot of philosophical basic’s knowledge such as ontology, epistemology and acciology. Researcher in the implementation step has not only known how do the research better, but how to get some literatures for his/her own knowledge from other researcher. Researcher in the reporting step has developed a research reporting format in its own institution tradition. Every educational institution has developed a research reporting format on its own traditions; depend on level of education and particular scientific specification.